Pengaruh Layanan Samsat Keliling, E-Samsat, Sanksi Perpajakan dan Kesadaran terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Batang - Fitri Maysaroh; Feri Tristiawan; Imtiyaz Farras Mufidah (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
The level of motor vehicle taxpayer compliance is still not optimal. This is still found in motor vehicles in Batang Regency that do not pay taxes, either due to deliberate factors or administrative and technical constraints. This study aims to examine the effect of mobile Samsat services, E-Samsat, tax sanctions, and awareness on taxpayer compliance in Batang Regency. This study uses a quantitative method by conducting a sampling survey from a number of populations and using a questionnaire. The analysis tool used IBM SPSS Statistics 25. Based on the results of the study, the mobile Samsat service does not have a significant effect on taxpayer compliance. Due to the limited number of mobile Samsat units and operating hours, it is hoped that the Batang Regency government will take a policy of extending operating hours, especially on holidays. E-Samsat does not have a significant effect on taxpayer compliance. Due to the lack of socialization and impacting application access is hampered by server downtime. Taxpayers feel the procedure is too complicated, it is hoped that the Batang Regency government will hold e-Samsat socialization. Tax sanctions have a positive and significant effect on taxpayer compliance. The stricter the sanctions applied by the tax authorities, the higher the level of taxpayer compliance. Taxpayer awareness has no significant impact on taxpayer compliance, due to a lack of knowledge and understanding of the importance of taxes. Local governments must consistently support the public in improving taxpayer compliance through proactive service innovations, friendly, accountable, and customer satisfaction-oriented services.